Engineering of a miniaturized, robotic clinical laboratory. Issue 1 (19th January 2018) - Nourse, Marilyn B.; Engel, Kate; Anekal, Samartha G.; Bailey, Jocelyn A.; Bhatta, Pradeep; Bhave, Devayani P.; Chandrasekaran, Shekar; Chen, Yutao; Chow, Steven; Das, Ushati; Galil, Erez; Gong, Xinwei; et al.
Abstract: The ability to perform laboratory testing near the patient and with smaller blood volumes would benefit patients and physicians alike. We describe our design of a miniaturized clinical laboratory system with three components: a hardware platform (ie, the miniLab) that performs preanalytical and analytical processing steps using miniaturized sample manipulation and detection modules, an assay‐configurable cartridge that provides consumable materials and assay reagents, and a server that communicates bidirectionally with the miniLab to manage assay‐specific protocols and analyze, store, and report results (i.e., the virtual analyzer). The miniLab can detect analytes in blood using multiple methods, including molecular diagnostics, immunoassays, clinical chemistry, and hematology. Analytical performance results show that our qualitative Zika virus assay has a limit of detection of 55 genomic copies/ml. For our anti‐herpes simplex virus type 2 immunoglobulin G, lipid panel, and lymphocyte subset panel assays, the miniLab has low imprecision, and method comparison results agree well with those from the United States Food and Drug Administration‐cleared devices. With its small footprint and versatility, the miniLab has the potential to provide testing of a range of analytes in decentralized locations.